Analisis Diskursus Kebijakan Vasektomi sebagai Prasyarat Bantuan Sosial: Studi Komparatif Perspektif Pragmatisme Politik dan Normatif Religius - Pratama, Wahyu Aji; M. Saeful Amri (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2025)
The vasectomy controversy as a prerequisite for social assistance triggered by the statement of West Java Governor Dedi Mulyadi has caused a debate between pragmatic and religious perspectives in Indonesia. This study aims to analyze the construction of the pro-con arguments for vasectomy through the debate between Adi Armando and K.H.Kholil Nafis at the "Democracy Record" event on May 6, 2025. The research method uses library research with a descriptive qualitative approach and critical discourse analysis of the Norman Fairclough model which analyzes textual dimensions, discursive practices, and social practices. Data was obtained from transcripts of television shows, online news articles, policy documents, and MUI fatwas. The results of the study show that Adi Armando builds utilitarian arguments based on economic efficiency and "rational choice", while Kholil Nafis uses theological arguments that emphasize the concepts of fitrah and maqashid sharia. This debate reflects the tension between practical benefits and sharia normative provisions in regulating reproductive aspects, as well as implications for the structure of marital rights and obligations in Islamic family law which requires alternative solutions based on economic empowerment and temporary contraceptive methods.